Pola Hubungan Petani Karet Dengan Pedagang Pengumpul di Desa Pulau Busuk Jaya Kecamatan Inuman Kabupaten Kuantan Singingi - Bamba Indalis; Evy Maharani; Shorea Khaswarina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to identify patterns of marketing channels made ​​by farmer of rubber at Pulau Busuk Jaya village, analyze the efficiency of the marketing of rubber at Pulau Busuk Jaya village, knowing the social relationship between the Tauke and the farmer of rubberand knowing theinterest and impeller factors of farmers to sell the rubber to the Tauke. The results showed that the marketing channels that occurred in the Pulau Busuk Jaya village consists of two marketing channels, namely channel 1 of the traders ( Tauke ) to wholesalers ( outside the village ) and go directly to the PT. Agrolestari Kuantan Singingi and on channel 2 of the traders ( Tauke ) go to the PT. Agrolestari Kuantan Singingi.Social relations that occur between the farmer of rubberand the Tauke which is a measure of the size of wealth, the size of honor, power and authority, size and knowledge. The interest and impeller factors of rubber farmer sell to the Taukeis influenced by several factors of which the interest factor that is price,provision of capital, social relation between farmer and traders (Tauke) appropriate bargaining system and the trust factor. Then the impeller factor is the relationship of debt, the amount of production and sources of funding ). Keywords: Marketing, efficiency, social relations between traders and farmers.